ENTREPRENEURIAL SELF-EFFICACY, PERCEIVED FAMILY SUPPORT, DAN ENTREPRENEURIAL INTENTION PADA MAHASISWA - Agata Sofia; Ersa Lanang Sanjaya (Psibernetika, 2021)
This studi aimed to examine entrepreneurial self-efficacy and perceived family support together as predictors of entrepreneurial intention of college student in Surabaya. A quantitative approach with a correlational design was used in this study. The participant of this study was 244 undergraduate students in Surabaya. The sampling technique used in the study was convenience sampling. The instruments used to measure the variables were Entrepreneurial Intention Questionnaire (Liñán & Chen, 2009), Entrepreneurial Self-Efficacy Scale (Mcgee, Peterson, Mueller, & Sequeira, 2009), and Perceived Family Support Scale (Shen, Osorio, & Settles, 2017). All of the scales were adapted into Indonesian. Result of the multiple regression analysis suggested that entrepreneurial selfefficacy and perceived family support simultaneously predicted entrepreneurial intention (R2 = 0,310, p < 0,05). The results of simple regression test showed a influence between entrepreneurial self-efficacy and entrepreneurial intention by controlling perceived family support (r = 0,482; R2 = 0,232; p < 0,05).The results of simple regression test also showed a positive relationship between perceived family support and entrepreneurial intention by controlling entrepreneurial self-efficacy (r = 0,393; R2 = 0,154; p < 0,05)